TEKNIK PEMERIKSAAN CT-SCAN 3D TULANG WAJAH DENGAN KLINIS SUSPECT TRAUMA MEDULLA SPINALIS DI INSTALASI RADIOLOGI RS AWAL BROS PANAM - Riana Riau azzahrah (LPPM Universitas Awal Bros, 2024)
Spinal cord trauma is injury to the spine, either directly or indirectly, which can cause lesions in the spinal cord, resulting in neurological disorders, disability and even death. When applied in one of the pathologies, namely spinal cord trauma, CT-Scan can see an anatomical picture of the head in axial slices and the image can be reformatted into 3 dimensions to see the skull bones more clearly without being obstructed by the surrounding tissue. In this research, the author wants to know the procedure for carrying out CT-Scan examination techniques of the head with clinical suspicion of spinal cord trauma. This research used descriptive method by observation of the patient in Awal Bros Panam. In conclusion, in the 3D CT-Scan examination procedure of facial bones at the Awal Bros Panam Hospital with the theory contained in the book